2003
DOI: 10.1038/sj.cgt.7700592
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy for hepatocellular carcinoma using non-viral vectors composed of bis guanidinium-tren-cholesterol and plasmids encoding the tissue inhibitors of metalloproteinases TIMP-2 and TIMP-3

Abstract: Metalloproteinases (MMPs) and their natural inhibitors (TIMPs) contribute to the regulation of tumor microenvironment. Their expressions are deregulated in almost all human cancers. We report a novel approach to gene therapy of hepatocellular carcinoma (HCC), using repeated injections of DNA plasmids encoding the tissue inhibitors of metalloproteinases (TIMPs) TIMP-2 or TIMP-3, and a novel competent formulation of gene transfer based on nontoxic cationic cholesterol derivatives. The new gene delivery system wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 32 publications
1
17
0
1
Order By: Relevance
“…Western blot and immunohistochemical assays showed that TIMP-3 is expressed at low levels both in human primary prostate cancer tissues and in prostate cancer cell lines. These data are consistent with other studies 7,11,21 that have shown loss or low expression of TIMP-3 in a variety of human tumors including prostate cancer. RT-PCR and western blot analyses showed that TIMP-3 is expressed at low levels in prostate cancer cell line PC-3M.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Western blot and immunohistochemical assays showed that TIMP-3 is expressed at low levels both in human primary prostate cancer tissues and in prostate cancer cell lines. These data are consistent with other studies 7,11,21 that have shown loss or low expression of TIMP-3 in a variety of human tumors including prostate cancer. RT-PCR and western blot analyses showed that TIMP-3 is expressed at low levels in prostate cancer cell line PC-3M.…”
Section: Discussionsupporting
confidence: 93%
“…4 Earlier data have shown that the absence of TIMP-3 in the host enhances tumor growth and angiogenesis. 5 The TIMP-3 protein can inhibit invasion and only TIMP-3 has the ability to induce apoptosis in select cell lines such as melanoma cells, 6 hepatocellular carcinoma, 7 breast cancer cells, 8 and lung cancer cells. 9 It has also been reported to suppress tumor growth through inhibition of endothelial cell migration and angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TIMP-3 overexpression showed inhibitory effects on tumor growth and angiogenesis in neuroblastoma, melanoma, and hepatocellular carcinoma tumor models (27)(28)(29)(30). Moreover, evidence is accumulating for a role of TIMP-3 in inducing apoptosis in various cell types by stabilization of death receptors such as Fas on the cell surface (31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…A volume of 500 ml CM from infected/uninfected K562 cells was placed in the lower chambers. 10 5 HUVECs, resuspended in serum-free RPMI-1640 containing 0.5% BSA, were placed in the upper chambers. After 4 h of incubation at 371C, cells in the lower chambers were collected, and counted by FACS at least three times.…”
Section: K562 Cells Growth and Invasion Assaysmentioning
confidence: 99%
“…TIMP-3 can inhibit all MMPs tested so far and its overexpression can drastically retard tumor angiogenesis, invasion and metastasis in mice model. [7][8][9][10] Recently, additional physiological functions have been attributed to TIMP-3, including inhibition of angiogenesis, 11 promotion of apoptosis 7,8,12,13 and the modulation of tumor necrosis factor a (TNF-a) signal transduction. 14 TIMP-3 gene is also considered to be a tumor suppressor gene, as its expression is silenced in different types of cancer due to the promoter hypermethylation.…”
Section: Introductionmentioning
confidence: 99%